Anatomical variations of the V 2 vertebral artery study by measuring the width of transverse foramen - Chanapa P. (2014)
Objective: To evaluate the incidence of anatomical variations of the V 2 segment of the vertebral artery (VA) using dry bones. Material and Method: The sample group was 181 cervical spines (equal 362 courses of VA), male 111 and female 70, average age 68 years old (range 26 to 95 years). The width of transverse foramens (TF) was visually inspected, starting at C7, looking upward to find the greatest width of TF meaning the beginning of V 2. Then, measurements were taken of the TF width (AP, ML) followed by measurements of those of one level below and above. Results: The VA entered the C6 TF in 89.0% (322 out of 362 courses). The variations level of entrance was observed in 11.0% of specimens (40 courses), with the level of C4, C5, and C7 TF in 1.1% (4 courses), 4.4% (16 courses), and 5.5% (20 courses), respectively. Nineteen out of 40 VA (47.5%) of variations were on the left side and twenty-one (52.5%) were on the right side. Twenty-three out of 40 VA (57.5%) of variations were men and seventeen (42.5%) were women. The areas of TF filled with VA were significantly larger than before and after the entrance level (p < 0.0001). Conclusion: Anatomical variations of the V 2 segment of the VA do exist at C4, C5, and C7. The awareness of this abnormality may reduce the risk of catastrophic intraoperative VA injury.